(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The cutting fluid is an integral part of any metal machining process, as it cools the workpiece, and the cutting tool flushes chips out of the cutting zone and lubricates the tool-to-workpiece interface. Still, the cutting fluid is potentially hazardous to both human and environmental health if misused or disposed of improperly. However, issues with production rate and environmental impact are brought to light by using an excessive quantity of cutting fluids. Manufacturers strive for a less hazardous workplace and lower production costs by using less cutting fluid in their machining processes. Minimum quantity lubrication (MQL), in which we feed the lubricant at a highly modest flow rate to the machining zone, is a practical approach to reaching this objective. There is proof that the MQL method may be used to accomplish "Green Machining" since it aligns with the standards set forth by that term. “Since this is the case, this research examines the outcomes of MQL in turning, drilling, grinding, and milling applications using mineral oils (base oils), vegetable oils (synthetic oils), and Nanofluids.” Compared to flood lubrication, the MQL approach has shown to be effective in the same situations.